HUBUNGAN KADAR GULA DARAH DENGAN INSOMNIAPADA PENDERITA DIABETES MELITUS - Wahyuningsih, Atik Setiawan; Huriah, Titih; Sari, Novita Kurnia (The Indonesian Journal of Health Science, 2016)
Background: Polyuria is one sign that appears of patients with diabetes mellitus. Nocturia that occurs in patients with diabetes mellitus can cause sleep disturbances break. The impact of a decline in the quality of sleep can disruption of activity in the next day may even cause an accident that means. This study aims to determine the relationship insomnia and blood sugar levels in people with diabetes mellitus (DM). Methods: This study was correlational with cross sectional approach. Using purposive sampling. Samples were taken according to inclusion and exclusion criteria. Measuring instrument used is the Insomnia Severity Index (ISI) and glucometers. Analyzed by non-parametric correlation Spearman's rho. Result: Spearman's rho has shows the value 0.000 and the strength of the relationship 0.633. Conclusion:  This researchhave shown an correlation between increase blood sugar levels with insomnia Suggestion: For health care providers are expected in the provision of treatment is not only focused on the management of blood sugar, but also in the management of insomnia